Proceedings of the Ninth ACM International Conference on Web Search and Data Mining 2016
DOI: 10.1145/2835776.2835820
|View full text |Cite
|
Sign up to set email alerts
|

Improving IP Geolocation using Query Logs

Abstract: IP geolocation databases map IP addresses to their geographical locations. These databases are important for several applications such as local search engine relevance, credit card fraud protection, geotargetted advertising, and online content delivery. While they are the most popular method of geolocation, they can have low accuracy at the city level. In this paper we evaluate and improve IP geolocation databases using data collected from search engine logs. We generate a large ground-truth dataset using real… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…The generic results lead to nationwide websites where the user has to requery for more specific restaurants in their area, while the personalized results directly list restaurants tailored to a specific location. Previous work has shown that personalizing results to a user's location leads to increased user satisfaction and conversely that missing location information leads to user dissatisfaction [4,14,37]. IP geolocation databases are also used in many other applications, including:…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The generic results lead to nationwide websites where the user has to requery for more specific restaurants in their area, while the personalized results directly list restaurants tailored to a specific location. Previous work has shown that personalizing results to a user's location leads to increased user satisfaction and conversely that missing location information leads to user dissatisfaction [4,14,37]. IP geolocation databases are also used in many other applications, including:…”
Section: Introductionmentioning
confidence: 99%
“…Related work has shown that while they have high coverage, commercial databases are sometimes inaccurate or are missing location information for some IP ranges [17,26,47,54]. Our own past work has demonstrated that the city-level accuracy of geolocation databases is less than 70% in 10 major countries [14]. Furthermore, the methods they use to derive their databases from these raw data sources are proprietary and therefore impossible to properly reproduce and expand upon in an academic settings.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that these databases are unsatisfactory, and there is considerable room for improvement. Reference [7] evaluated 3 popular databases and noted that the average accuracy at the city level of these databases is less than 70%.…”
Section: Introductionmentioning
confidence: 99%
“…In [20,21], the authors analysed the distribution characteristics of IP address blocks of different geographic granularity in mainland China, compared the data consistency between multiple IP location database, verified the accuracy of the IP location database using a small number of existing landmarks, and improved the accuracy of the database by clustering IP blocks at different locations. For improving the accuracy of database, location data collected from search engine logs [22], IP allocation strategy of ISPs, urban areas, and population [23] were introduced into the database evaluation methods. Using those methods improve the accuracy at city level, but there are inadequacies in evaluating fine-grained (e.g., street level) locations.…”
Section: Introductionmentioning
confidence: 99%